Surviying Brexit social economic impact on the UK a narratical study (2016- 2020) - Bouhali, Mohammed; Kourdourli, Abdelkade (Faculty of Letters and Foreign Languages Department of English, 2023)
My dissertation deals with the issue of Brexit as a major event in the contemporary history of the United Kingdom. The aim of this study is to examine the socio-economic impacts of Brexit on the United Kingdom. The study adopts a qualitative, descriptive, and analytical approach.The first finding of the study is that the relationships of the UK with the European Union were ambivalent since the UK joined the EU in 1973. The investigation shows that European immigration is a major cause of Brexit. Another finding suggests that Brexit allows the UK to maintain a socio-cultural stability. This study has found that generally the UK has gained more independence and more prosperity as regards its economy. Although this study has focused on the positive impact of Brexit on the UK, the findings may well have a bearing on Scottish independence, the impact of Brexit on the EU, and even the future of the EU